Spectrum of prenatally diagnosed neural tube defects at a tertiary referral hospital in North India: a retrospective cohort study - Malik, Nisha; Singhal, Savita Rani; Nanda, Smiti; Sirohiwal, Daya; Dahiya, Pushpa; Bharti, Anita (International Journal of Contemporary Pediatrics, 2020)
Background: Neural tube defects, although largely preventable, constitute an important cause of neonatal mortality and morbidity. The study aimed to identify incidence rate, demographic profile, risk factors, and pregnancy outcomes of women with prenatally diagnosed NTDs. Methods: This retrospective cohort study reviewed the case records of all antenatal women admitted in labour ward of Pt. B.D Sharma postgraduate institute of medical sciences, Rohtak, India with the prenatal diagnosis of NTDs on ultrasound from August 2018 to January 2020. The sociodemographic details, risk factors, obstetric history and pregnancy outcomes were noted. The mean, standard deviation and range values were calculated for normally distributed data. Categorical data were presented as frequency and percentage values. Results: From a total of 21,187 births, 90 had neural tube defects, making an incidence rate of 4.3 per 1000 births. Out of the 86 included cases of NTDs, 46.5% (n=40) had anencephaly, 45.3% (n=39) spina bifida, 5.8% (n=5) encephalocele and 2.3% (n=2) had mixed defects. Majority (69.7%, n=60) of the women were multigravida with a mean age of 24.9±4.2 years. Preconceptional folic acid intake was found in merely 2.3% (n=2) cases and during first trimester of pregnancy in 39.5% (n=40) cases. About 61.6% (n=53) cases who presented at ≤20 weeks gestation underwent pregnancy termination while 38.3% (n=33) had vaginal delivery, of which majority (90.7%) were still births. Conclusions: NTDs are one of the commonest preventable congenital anomalies. Ensuring periconceptional folate supplementation to women-either by food fortification, dietary modification and public awareness is urgently required.